CHATGPT IN THE ACADEMIC WRITING CLASSROOM - Ida Royani; Mujahidah Rizki Sihombing (Esteem Journal of English Education Study Programme, 2024)
Artificial intelligence has made inroads into the field of education, particularly with regard to academic writing for language learners. As ChatGPT demonstrates in the learning process, AI is able to react in a highly natural language and have conversations in a variety of scenarios. This essay explores how ChatGPT can support the academic writing process through a rigorous literature review. It demonstrates that ChatGPT may generate interest across a wide linguistic spectrum, gather the most recent knowledge to assist with a range of activities, reply to inquiries with sincere dialogue, and improve writing skills. It also figures out the connection of process of writing based on (Nang et al., 2008) by using ChatCPT companions. Meanwhile, wisdom in use of it in the learning environment should be taken into consideration because of losing creativity and lack of conversational practice. Therefore, it is suggested to learners and teachers to be careful and wise to interact with this technological tool, since humans can only provide judgement and verification maker.